2019
DOI: 10.1128/jb.00602-18
|View full text |Cite
|
Sign up to set email alerts
|

DNA Binding and Sensor Specificity of FarR, a Novel TetR Family Regulator Required for Induction of the Fatty Acid Efflux Pump FarE in Staphylococcus aureus

Abstract: Divergent genes in Staphylococcus aureus USA300 encode the efflux pump FarE and TetR family regulator FarR, which confer resistance to antimicrobial unsaturated fatty acids. To study their regulation, we constructed USA300 ΔfarER, which exhibited a 2-fold reduction in MIC of linoleic acid. farE expressed from its native promoter on pLIfarE conferred increased resistance to USA300 but not USA300 ΔfarER. Complementation of USA300 ΔfarER with pLIfarR also had no effect, whereas resistance was restored with pLIfar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 55 publications
(74 reference statements)
2
17
0
Order By: Relevance
“…It is now evident that these commonly encountered environmental signals confer enhanced resistance to antimicrobial uFFA, with different genetic requirements depending on acidic or nonacidic growth conditions and exposure to calcium or subinhibitory antimicrobial peptides. We previously found that the RND family efflux pump FarE was required for S. aureus resistance to antimicrobial uFFA (5,11), and in our present work, this requirement was maintained under nonacidic growth conditions for enhanced resistance to linoleic acid in unbuffered TSB supplemented with calcium. However, at acidic pH, enhanced resistance to both C 18:2 and C 16:1 uFFA was dependent on GraS and GraS-dependent expression of MprF.…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…It is now evident that these commonly encountered environmental signals confer enhanced resistance to antimicrobial uFFA, with different genetic requirements depending on acidic or nonacidic growth conditions and exposure to calcium or subinhibitory antimicrobial peptides. We previously found that the RND family efflux pump FarE was required for S. aureus resistance to antimicrobial uFFA (5,11), and in our present work, this requirement was maintained under nonacidic growth conditions for enhanced resistance to linoleic acid in unbuffered TSB supplemented with calcium. However, at acidic pH, enhanced resistance to both C 18:2 and C 16:1 uFFA was dependent on GraS and GraS-dependent expression of MprF.…”
Section: Discussionsupporting
confidence: 66%
“…Strain and plasmid construction. Genetic manipulation of S. aureus was conducted according to established guidelines and as described in previous work (4,11,65). All recombinant plasmids were initially constructed in E. coli DH5␣.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the environments where some pathogenic bacteria must thrive in, such as the skin or the mouth, contain unsaturated fatty acids and therefore they need more advanced protection mechanisms such as fatty acid export systems (Choi et al, 2013; Parsons et al, 2012). In the Gram‐positive bacterium Staphylococcus aureus , an opportunistic pathogen found on the skin, a fatty acid export system was found when screening for strains resistant to linoleic acid (Alnaseri et al, 2019). The strain S. aureus FAR7 showed a mutation in the transcription factor farR , which led to the upregulation of the farE gene, encoding an efflux pump from the RND superfamily.…”
Section: Fatty Acid Transport In Bacteriamentioning
confidence: 99%